GlycA, a novel pro‐inflammatory glycoprotein biomarker is associated with mortality: results from the PREVEND study and meta‐analysis. (24th July 2019) - Gruppen, E. G.; Kunutsor, S. K.; Kieneker, L. M.; van der Vegt, B.; Connelly, M. A.; de Bock, G. H.; Gansevoort, R. T.; Bakker, S. J. L.; Dullaart, R. P. F.
Abstract: Background: Chronic diseases are associated with an inflammatory response. We determined the association of two inflammatory markers, GlycA and high‐sensitivity C‐reactive protein (hsCRP), with overall and cause‐specific mortality in a cohort of men and women. Methods: Cox regression analyses were used to examine associations of GlycA and hsCRP with all‐cause, cancer and cardiovascular mortality in 5526 subjects (PREVEND cohort; average follow‐up 12.6 years). Results: GlycA was associated with all‐cause mortality ( n  = 838), independent of clinical risk factors and hsCRP (hazard ratio 1.43 [95% confidence interval (CI): 1.09–1.87] for top versus bottom quartiles). For hsCRP, the association with all‐cause mortality was nonsignificant after adjustment for GlycA. GlycA and hsCRP were associated with cancer mortality in men ( n  = 248), but not in women ( n  = 132). Neither GlycA nor hsCRP was independently associated with cardiovascular mortality ( n  = 201). In a meta‐analysis of seven population‐based studies, including 8153 deaths, the pooled multivariable‐adjusted relative risk of GlycA for all‐cause mortality was 1.74 (95% CI: 1.40–2.17) for top versus bottom quartiles. The association of GlycA with all‐cause mortality was somewhat stronger than that of hsCRP. GlycA and hsCRP were not independently associated with cardiovascular mortality. The associations of GlycA and hsCRP with cancer mortality were present in men, but not in women. Conclusions: GlycA is significantly associated with all‐cause mortality. GlycA and hsCRP were each not independently associated with cardiovascular mortality. The association of GlycA and hsCRP with cancer mortality appears to be driven by men. Abstract :